Faecalibacterium prausnitzii Attenuates DSS‐Induced Colitis by Inhibiting the Colonization and Pathogenicity of Candida albicans. Issue 21 (7th October 2021) - Mao, Xiaqiong; Ma, Jingjing; Jiao, Chunhua; Tang, Nana; Zhao, Xiaojing; Wang, Di; Zhang, Yue; Ye, Ziping; Xu, Chenjing; Jiang, Jingyue; Wu, Shasha; Cui, Xiufang; et al.
Abstract : Scope: Intestinal commensal microbiota interactions play critical roles in the inflammatory bowel disease (IBD) development. Candida albicans (CA) can aggravate intestinal inflammation; however, whether Faecalibacterium prausnitzii (FP) can antagonize CA is unknown. Methods and Results: CA are co‐cultured with bacteria (FP and Escherichia coli (EC)), bacterial supernatant, and bacterial medium, respectively. Then, the CA hyphae‐specific genes' expression and CA cells' morphology are investigated. The Nod‐like receptor pyrin‐containing protein 6 (NLRP6) inflammasome, inflammatory cytokines, and antimicrobial peptides (AMPs) production are evaluated in intestinal epithelial cells pre‐treated with bacteria, bacterial med, and bacterial supernatant and exposed without or with CA. Both bacteria significantly prohibit CA numbers, while only FP and FP supernatant prohibit the transformation and virulence factors (extracellular phospholipase, secreted aspartyl proteinase, and hemolysin) secretion of CA in a co‐culture system compared with media controls. Further, FP and FP supernatant promote the production of the NLRP6 inflammasome, interleukin (IL)‐1β, IL‐18, and antibacterial peptides (β‐defensin (BD)‐2 and BD‐3) and inhibit in vitro and in vivo CA growth and pathogenicity, and alleviate DSS‐colitis in mice, while EC do not show the similar effect. Conclusion: FP improve intestinal inflammation by inhibiting CA reproduction, colonization, and pathogenicity and inducing AMP secretion in the gut. This study uncovers new relationships between intestinal microbes and fungi in IBD patients. Abstract : FP prohibit the hyphal transformation and virulence of Candida albicans (CA) in intestinal lumen. Further, Faecalibacterium prausnitzii can promote the production of the Nod‐like receptor pyrin‐containing protein 6 inflammasome, interleukin (IL)‐1β, IL‐18, and antibacterial peptides (β‐defensin (BD)‐2 and BD‐3) in intestinal epithelial cells and then inhibit in vitro and in vivo CA growth, colonization, virulence, and alleviate intestinal inflammation. All parts of the GA image are original.